(untitled) (Homoeopathy for All, 2026)
Preschool years, ranging from 3 to 6 years of age, mark a period of rapid physical, cognitive, and emotional development.1,2 Optimal nutrition during this phase is vital not only for maintaining adequate health but also for ensuring proper growth dynamics, which includes height gain, weight gain, and brain development.3 Monthly nutritional support programs, especially in low resource settings, have emerged as an essential intervention to bridge dietary gaps, prevent malnutrition, and promote holistic development in children.4